Primary Care Psychiatry eConsults at a Rural Academic Medical Center: Descriptive Analysis - Jade Avery; Dennis Dwan; Gillian Sowden; Matthew Duncan (JMIR Publications, 2021)
BackgroundPrimary care providers serve a crucial role in addressing the mental health needs of many patients. However, there are times when input from a psychiatric specialist may be helpful in supporting the mental health care provided in primary care. Psychiatry eConsults can serve as a valuable tool in providing specialist advice for primary care physicians when direct referral to specialty care is not readily available. ObjectiveThe goal of this study is to evaluate the content and implementation of psychiatric eConsults by primary care providers in a rural academic medical center. MethodsThis is a retrospective review of 343 eConsults placed between May 2016 and February 2019 by primary care providers at a single academic medical center. The content of eConsult requests, including patient diagnosis, consult question type, specialist recommendations, patient demographics, the distance of patient and primary care providers from the consulting provider, rate of implementation of the recommendation, and response time, were analyzed. ResultsThe most common diagnoses associated with eConsults were depression (162/450, 36%) and anxiety (118/450, 26%). The most commonly asked eConsult question was regarding medication management, including medication choice, side effects, interactions, and medication taper (288/343, 84%). More than one recommendation was included in 76% (259/343) of eConsults, and at least one recommendation was implemented by the primary care provider in 94% (282/300) of eConsults. The average time to respond to an eConsult was 26 hours. ConclusionsThis study demonstrates that psychiatry eConsults can be conducted in a timely manner and that primary care providers implement the recommendations at a high rate.